Evaluation and delivery of disease-resistant and micronutrientdense sweetpotato varieties to farmers in Uganda - Ssemakula, G.N.; Niringiye, C.; Otema, M.A.; Kyalo, Gerald; Namakula, J.; Mwanga, Robert O.M. (2014)
Uganda is among the African countries reported to be at high risk of Vitamin A deficiency (VAD) with prevalence of VAD among children and women at 28 and 23%, respectively. Promoting orange-fleshed sweetpotato (OFSP) (Ipomoea batatas) rich in Vitamin A will play a significant role in combating VAD. However, sweetpotato virus disease is a major constraint to OFSP. The National Crops Resources Research Institute (NaCRRI) under took research on improvement, evaluation and delivery of promising OFSP to farmers. Selected parents with complimentary traits are planted to a crossing block annually and true seed is harvested and used to establish nurseries the plants of which are individually screened for reaction to SPVD, Alternaria blight, and depth of the orange colour in the root flesh. Promising selections are evaluated through a series of verification multi-locational trials on-station. Selections are subsequently advanced onfarm to test their performance under farmer managed conditions and for their acceptability by farmers and consumers for both food and other uses. To date nine OFSP varieties have been released and disseminated to farmers.Generally, most of the released OFSP varieties are susceptible to weevils (Cylas spp.), but moderately resistant to both SPVD and Alternaria blight.